Bullying In Education In The Perspective Of Hadith - Kamaruddin, Ratna; Amin, Muhammadiyah; Ahmad, La Ode Ismail; Fatmal, Abd. Bashir (Institut Agama Islam Sumatera Barat Pariaman, 2024)
Bullying in education is a despicable act and is prohibited by Islam because it can hurt the victim physically and mentally. The meaning of Bullying is an act of threatening, scaring bodily or spiritually against someone due to one’s superiority attitude, so that they feel entitled or powerful to intimidate others. This study examines Bullying from the perspective of the Prophetic Hadith on the phenomenon of Bullying. This study seeks to find the significance of the phenomenon of Bullying with the hadith and the relevance of exploring the preventive measures offered by the hadith of the Prophet. The method used is descriptive-analytical. The results of this research are: 1) The Hadith narrated by Ibn Majah generally explains how the Prophet’s Hadith views Bullying as leading to degrading behavior. The word ihtiqar has a meaning correlation to the orientation of Bullying behavior, namely degrading, Hadith narrated by Sahih Muslim is also about degrading other people’s behavior, and Hadith Bukhari about one’s life and honor must be protected, respected and guarded; 2) the normative relevance of the phenomenon of Bullying is the prohibition of mutual envy, hatred, oppression, neglect and contempt for other Muslims, the prohibition of degrading others which can be the root of the division of Muslims, and no one has the right to kill, insult, damage and injure others without reasons justified by Islamic law.